Analisis Suhu Permukaan Tanah dan Kelembaban Tanah Menggunakan Interpretasi Citra Landsat 8 OLI Diperkebunan Nanas PT. Great Giant Pineapple - Briany, Adelia Dewi; Ridwan, Ridwan; Amien, Elhamida Rezkia; Asmara, Sandi (Jurnal Agricultural Biosystem Engineering, 2025)
PT. Great Giant Pineapple (GGP) is the largest processed pineapple producer in Indonesia, cultivating pineapples in a long-term monoculture system, which has the potential to cause land degradation. To understand land conditions more accurately, this study integrates remote sensing technology with Landsat 8 OLI/TIRS satellite image analysis to measure land surface temperature (LST) and soil moisture using the Soil Moisture Index (SMI). Field data were collected from a 2000-hectare area in PT. GGP and analyzed using ArcGIS and Google Earth Pro software. The results showed that the NDVI values ranged from -0.157 to 0.634, with significant variations in value distribution from 2021 to 2023. LST analysis revealed a minimum soil temperature of 7.15°C and a maximum of 33.38°C, with temperature patterns influenced by seasonal changes and rainfall. Meanwhile, soil moisture based on SMI exhibited fluctuations with a minimum value of -8.34 and a maximum of 1.00, reflecting variations in soil water content due to environmental factors. Validation of satellite image analysis with field measurements demonstrated a strong correlation, supporting the effectiveness of remote sensing in mapping soil moisture and land surface temperature in pineapple plantations. Keywords: Remote sensing, Landsat 8, soil moisture, land surface temperature, pineapple.